Islamic Republic of Mauritania : Staff Report for the 2002 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper focuses on the Islamic Republic of Mauritania's 2002 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criteria. Performance under the PRGF-supported program was solid in 2001, reflecting sound economic policies and greater ownership. Two of three structural performance criteria were met. The IMF staff supports the authorities' macroeconomic policies for 2002 with emphasis on improved macroeconomic policy coordination, particularly monetary and exchange rate policies.